LITERATURE REVIEW : PELEPASAN INFORMASI MEDIS KEPADA PIHAK ASURANSI - Almas Ummi Fatharina; Sri Sugiarsi; Trismianto Asmo Sutrisno (Indonesian Journal of Health Information Management, 2021)
Abstract Release of medical information must be subject to applicable procedures and must be with the patient's consent. Patients must make a stamped written statement that has authorized a third party to request medical data from a doctor. The purpose of this study is to determine the policy of releasing medical information and the flow of procedures for releasing medical information to the insurer. The research method in this study is to use a literature review design, namely research that examines research articles on the release of medical information to insurance parties by comparing, summarizing, and drawing conclusions. The search strategy used keywords and operator bundles used in this study, namely "medical records" or "information release" or "insurers". The result of the research is that a hospital is in the process of releasing medical information using policies in the form of SOPs, cooperation agreements with insurance parties, and orally. In addition, there are hospitals that have different procedures for releasing medical information because they do not only serve one insurance party, but there are several insurance parties that are served such as BPJS, Jasa Raharja, and Askes. However, in the process of releasing medical information, there are hospitals that are not yet in accordance with the flow of medical information release procedures that have been determined by the Hospital. Therefore, the hospital conducts outreach on the flow of procedures for releasing medical information so that the officer in charge has a better understanding of the release of medical information. Keyword : medical records, information release, insurers Abstrak Pelepasan informasi medis harus mengacu pada prosedur yang berlaku dan harus dengan persetujuan pasien. Pasien harus membuat pernyataan tertulis bermaterai bahwa telah memberi kuasa kepada pihak ketiga untuk meminta data medis dari dokter. Tujuan penelitian ini adalah untuk mengetahui kebijakan pelepasan informasi medis dan alur prosedur pelepasan informasi medis kepada pihak asuransi. Metode penelitian dalam penelitian ini adalah menggunakan desain literature review yaitu penelitian yang mengkaji artikel-artikel penelitian tentang Pelepasan Informasi Medis Kepada Pihak Asuransi dengan cara membandingkan, meringkas, dan mengambil kesimpulan. Strategi pencarian menggunakan keyword dan booelan operator yang digunakan dalam penelitian ini yaitu “rekam medis” or “pelepasan informasi” or “pihak asuransi”. Hasil penelitian terdapat Rumah Sakit yang dalam proses pelepasan informasi medis menggunakan kebijakan dalam bentuk SOP, perjanjian kerjasama dengan pihak asuransi, dan secara lisan. Selain itu terdapat Rumah Sakit memiliki alur prosedur pelepasan informasi medis yang berbeda-beda karena tidak hanya melayani satu pihak asuransi saja, tetapi ada beberapa pihak asuransi yang dilayani seperti BPJS, Jasa Raharja, dan Askes. Akan tetapi dalam proses pelepasan informasi medis terdapat Rumah Sakit yang belum sesuai dengan alur prosedur pelepasan informasi medis yang telah ditentukan oleh Rumah Sakit. Oleh karena itu pihak Rumah Sakit melakukan sosialisasi mengenai alur prosedur pelepasan informasi medis agar petugas yang bertanggungjawab lebih paham mengenai pelepasan informasi medis.